(untitled) (Journal of Eye Movement Research, 2010)
In the present study, the role of visual attentional processes for working memory performance in a sample of 6-year-olds was investigated. This was done by combining an individual differences approach with an experimental manipulation: For the individual differences approach, participants were grouped based on their performance in a classical interference control task, and their working memory skills were systematically compared. For the experimental manipulation, the need to control interference while performing a working memory task was increased in one condition through presentation of distracting stimuli. In a between-subject design performance in this condition was contrasted with a control condition without distractors. Additionally, fixation time during stimuli presentation were quantified by tracking participants` gazes. Results revealed that children with higher interference control skills showed superior working memory performance. Increasing the need to inhibit attention towards task-irrelevant information through presentation of distractors decreased working memory performance. The present study offers supporting evidence for a close relationship between young children`s working memory and attention.